Pengembangan Potensi Desa Girijati Dalam Sektor Pariwisata dan Sumber Daya Manusia Sebagai Pemandu Wisata - Nernere, Maria Setyaningsih (Jurnal Atma Inovasia, 2022)
Girijati is a village located in Purwosari, Gunungkidul, Daerah Istimewa Yogyakarta. There are lots of potential resources in Girijati, such as their nature, human resource, and also tourist attractions. Some of the tourist attractions in Girijati are Parangendog Beach, Gembirowati Temple, Sendang Beji, etc. In fact, the development of these tourist attractions requires high human resources quality too, for example, the demand of tour guide. It would be beneficial for Girijati village, if they develop the tourist attractions by making a tourist package from their potentials, such as the tourist attractions in Girijati. There are 3 segmentations for the packages, based on the demographic, psychographic, and the beneficial. The tourist packages were also segmented by the duration of the tour, the purpose, the tour by interest, and the offered facilities. A tour guide needs to guide the tourist and also to gives the right information related to the attraction that will be visited. Some important things that should be considered as a tour guide are the code of ethics, good communication skill with tourists, body language, and knowledge about the attraction.